Tungsten in the Second World War: China, Japan, Germany, the Allies and Iberia (Comillas Journal of International Relations, 2017)
This article studies the production, legal and illegal trade, and provisioning of strategic mineral wolfram/tungsten both by the Allies and the Axis during World War II. It analyzes the case the world’s largest producer of this mineral, China, the trade agreements signed by Chiang Kai-shek before the war with Nazi Germany, the USSR and Britain and their evolution during the global conflict. It also analyzes Japan, its difficulties in obtaining Chinese wolfram and its dependence on Korea. As for Nazi Germany, it studies its supply of Chinese ore until 1941 and later in the Iberian Peninsula, a trade made difficult by the Allied preventive purchases in Spain and Portugal. The article also studies the case of the US, its progressive auto provisioning in the Western Hemisphere, the airlift established between China and India to extract tungsten and distribution of amounts of it in Britain and the USSR. Finally, the article includes an assessment of the importance of tungsten within the set of strategic materials used by the contenders in the war and concludes that the Allied strategy hinder or prevent the provision of the enemy helped to reduce use and negatively affected the effectiveness of its machinery of war.
Keywords: Wolfram; tungsten; Second World War; Second Sino-Japanese War; Nazi Germany; Japan; the United States; Soviet Union; Britain; Franco Spain; Portugal; smuggling; runners blockade.